FORMATION OF STUDENTS' ORGANIZATION IN THEIR PROCESS EDUCATIONAL AND COGNITIVE ACTIVITIES (Pedagogy of Higher and Secondary Education, 2003)
Formation of Pupils’ Organization in the Process of their Science Researching Activity. The definition of the conception of the organization in science - researching activity is given. Its relations with the conceptions of self-organization; scientific approach to work and culture of mental activity aresubstantiated Inseparable ties of organization and science-researching activity are founded, it is also proved that the methods and means of formation of the quality mentioned depend on the type of academic activity. The peculiarities of science-researching activity of the senior pupils are. found out, the criteria of the definitions of the level of organization in different types of science-researching activity are developed. The definitions of criteria are based on the cognitive and regulating components of the position of the subject of learning.